Eksplorasi Nilai Pendidikan Lingkungan Cerpen Daring Republika: Kajian Ekokritik - Juanda (Jurnal Sosial Humaniora, 2025)
The purpose of this study is to explore the value of environmental education and interaction between characters and nature in the short stories of the Republika newspaper. This type of research is a qualitative study by describing descriptive or qualitative descriptive data. The data source comes from the Republika Newspaper which can be accessed in https: //lakonhidup.wordpress.com. The data focus on environmental phenomena in the short story of the 2015 to 2018 edition of Republika newspaper. The technique used is the content analysis technique. The data were analyzed using an ecocritical approach Grag Garrard (2004). Based on the results of the research, it was concluded that the republika short story contained an environmental theme whose proportions were very lacking. The dominant environmental phenomenon highlights natural and forest disasters. The value of Republika's short stories environmental education, namely: tree planting, reforestation of forests that have been exploited, the implementation of rules and regulations for deforestation, and animal conservation.